Retinal vascular occlusion risks during the COVID-19 pandemic and after SARS-CoV-2 infection - Hyo Song Park; Sunyeup Kim; Christopher Seungkyu Lee; Suk Ho Byeon; Sung Soo Kim; Seung Won Lee; Yong Joon Kim (Scientific Reports, 2023)
Abstract The coronavirus disease 2019 (COVID-19) has been reported to affect vascular networks including the eye. However, evidence on the causal relationship between COVID-19 infection and retinal vascular occlusions remains limited. This study aimed to determine the change in retinal vascular occlusion incidence during COVID-19 era and whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection induces retinal vascular occlusion. Retinal vein occlusion (RVO) and retinal artery occlusion (RAO) incidences during 2018–2019 and 2020–July 2021 were compared, those in confirmed and suspected COVID-19 patients diagnosed from 2020 to January 2021 were calculated, and those in COVID-19 patients during 180 days prior and 180 days after diagnosis were assessed. Additionally, the standardized incidence ratio of RVOs in COVID-19 patients was analyzed. Incidence rates per 100,000 people/year of RVO during 2018–2019 and 2020–2021 was 102.0 and 98.8, respectively. RAO incidence rates during 2018–2019 and 2020–2021 were 11.7 and 12.0, respectively. In both confirmed and suspected COVID-19 patients, the incidence of RVO and RAO did not change significantly from 180 days before to after diagnosis in the adjusted model. RVO incidence slightly decreased while RAO incidence increased during the COVID-19 pandemic. SARS-CoV-2 infection did not significantly increase RVO or RAO incidence.